Biodiversity Loss and Conservation of Natural Resources in Cold Desert Ecosystem of Himachal Pradesh, India - Poonam; Bawa, Rajan; Sankhyan, Hari Paul; Nayak, Dileshwar (Indian Forester, 2018)
The present investigation was conducted in village Goshal of District Lahaul and Spiti, (Himachal Pradesh), India, by differentiating the village into three ecosystems viz., Forest ecosystem, Alpine ecosystem and Agro ecosystem to carry out phytosociological studies. Each ecosystem was divided into nine different grids for sampling following quadrate method. Three quadrates were laid in each grid in all the three ecosystems for recording of phytosociological data. In forest ecosystem, among trees, the species of maximum occurrence was Juniperus recurva (IVI 62.89), while in alpine ecosystem Dactylis glomerata (IVI 62.49) dominated among grasses having maximum percentage contribution (20.83%), and Juniperus communis among shrubs. In agro ecosystem, Dactylis glomerata and Agropyron longearistatum among grasses were found to be the most dominating species with average IVI value of 50.70 and 49.30, respectively. Among agricultural crops, the maximum area was occupied by the cash crops like peas and potato. Peas were sown in 60.19 per cent of the total cropped area. It was observed that farmers have switched over to the cropping of cash crops which are economically beneficial and is affecting the present status of surrounding natural resources resulting in loss of biodiversity.